Imaging photon detectors and their use with single and multiple Fabry-Perot etalon systems for atmospheric wind measurements - McWhirter, Ian (UCL (University College London), 1993)
Imaging Photon Detectors are extremely sensitive imaging devices capable of detecting single photons of light. The Fabry-Perot etalon, a multiple beam interference device, is capable of detecting very small changes in the wavelength of light and is thus well suited to the determination of Doppler shifts. The combination of these two devices has enabled the realisation of a series of operational interferometers for the measurement of wind velocities in the upper atmosphere. This is achieved by measuring Doppler shifts in optical phenomena occurring at high altitudes. The instruments have been successfully deployed in Northern Scandinavia, North America and other locations world-wide. A full description of the component parts of the IPD and its associated electronics is presented. The theory and practical limitations of the device are discussed, together with a critical performance analysis of the complete imaging system. In addition to the IPDs for the Fabry-Perot interferometers, special types have been built for high time-resolution atmospheric lidar and a rocket-borne auroral imager. The Fabry-Perot etalon is described and the practical aspects of incorporating it into an interferometer are considered. The instruments are required to run unattended for extended periods, so particular care has been paid to long term aspects of stability, reliability and safe operation. Etalons can be tuned using piezo-electric transducers to vary the cavity length, in conjunction with capacitance sensors which determine the precise amount of movement. Such devices are termed capacitance stabilised etalons. These etalons can be combined in multiple etalon systems which provide greatly improved optical filtering. This allows measurements to be made against the higher background illumination encountered during daylight hours. Triple etalon interferometers have been built which have been flown on balloons in Texas and operated from the ground in Northern Sweden.